2017
DOI: 10.1007/s13202-017-0382-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation study on miscible EOR techniques for improving oil recovery in shale oil reservoirs

Abstract: Shale formations in North America such as Bakken, Niobrara, and Eagle Ford have huge oil in place, 100-900 billion barrels of oil in Bakken only. However, the predicted primary recovery is still below 10%. Therefore, seeking for techniques to enhance oil recovery in these complex plays is inevitable. Although most of the previous studies in this area recommended that CO 2 would be the best EOR technique to improve oil recovery in these formations, pilot tests showed that natural gases performance clearly excee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Both the contact area and exposure time of CO 2 to the matrix are higher in the laboratory than in the field . For natural gas EOR, higher porosity, natural fracture intensity, and diffusion rates were also beneficial (Table , entry 41). , However, the oil recovery performance of the natural gas was more sensitive to molecular diffusion than CO 2 and increased more dramatically with increases in diffusion rate. These results imply that natural gas is the preferred injection fluid when the permeability of the formation is less than 1 mD because CO 2 has higher molecular weight and needs larger pore throats to invade the matrix .…”
Section: Simulation Studies Related To Gas-based Eor In Ulrsmentioning
confidence: 99%
“…Both the contact area and exposure time of CO 2 to the matrix are higher in the laboratory than in the field . For natural gas EOR, higher porosity, natural fracture intensity, and diffusion rates were also beneficial (Table , entry 41). , However, the oil recovery performance of the natural gas was more sensitive to molecular diffusion than CO 2 and increased more dramatically with increases in diffusion rate. These results imply that natural gas is the preferred injection fluid when the permeability of the formation is less than 1 mD because CO 2 has higher molecular weight and needs larger pore throats to invade the matrix .…”
Section: Simulation Studies Related To Gas-based Eor In Ulrsmentioning
confidence: 99%
“…They also investigated their model for fractured gas condensate and showed that diffusion affected the condensate recovery. Alfarge et al 23 investigated the numerical simulation study on miscible EOR techniques for enhancing oil recovery in shale oil reservoirs. Their simulation results showed the significance of molecular diffusion in a gas injection on EOR for the studied reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…However, a field development plan is one of the crucial tasks that can enhance reservoir performance and maximize economic value that has not yet been mentioned in the case of basement reservoir. In recent years, many studies have focused on numerical simulation for improving oil recovery in unconventional reservoirs (Alfarge et al 2018;Izadmehr et al 2018). Alfarge et al (2018) introduced the way to select the best type of miscible gases to enhance oil recovery in shale oil reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have focused on numerical simulation for improving oil recovery in unconventional reservoirs (Alfarge et al 2018;Izadmehr et al 2018). Alfarge et al (2018) introduced the way to select the best type of miscible gases to enhance oil recovery in shale oil reservoirs. Furthermore, Izadmehr et al (2018) considered the injector rate, number and installation of submersible pumps to rank the development scenarios for the oil field.…”
Section: Introductionmentioning
confidence: 99%